Institutional work by market-shaping public actors. Issue 4 (24th July 2020) - Kaartemo, Valtteri; Nenonen, Suvi; Windahl, Charlotta
Abstract : Purpose: This study aims to identify institutional work mechanisms that public actors employ in market shaping. Design/methodology/approach: The paper uses an abductive theorizing process, combining a literature review with an empirical exploration of three different market-shaping contexts. Findings: The study identifies 20 granular mechanisms of institutional work that market-shaping public actors employ. These mechanisms are all potentially employable in creating, maintaining or disrupting markets. Institutional work vis-à-vis individual institutions may differ in direction from the institutional work vis-à-vis the market system. Public actors are not a homogeneous group but may have different values and support competing institutional logics even when operating in the same market. Research limitations/implications: The empirical data were limited to three cases in three small open economies. Data collected from other markets and with other methods would provide more rigorous insight into market-shaping public actors. Practical implications: The findings revealed institutional work mechanisms that public actors can use to shape markets. Companies wanting to engage public actors in market shaping should be aware of the values and institutional logics that influence market-shaping public actors. Originality/value: The paper unites and expands on the scattered knowledge regarding institutional work in market shaping. It illuminates and dissects the role of public actors in market shaping, challenging the reactive stance that is often assigned to them. The study provides a better understanding of how conflicting market views affect markets. It also brings insights into the interplay between market-shaping actions and the multiple levels of market systems.